Guidelines for the diagnosis and treatment of acute pancreatitis in China (2021). Issue 2 (7th June 2021) - Li, Fei; Cai, Shouwang; Cao, Feng; Chen, Rufu; Fu, Deliang; Ge, Chunlin; Hao, Chunyi; Hao, Jihui; Huang, Heguang; Jian, Zhixiang; Jin, Gang; Li, Ang; et al.
Abstract : Abstract: Acute pancreatitis (AP) is a common acute abdominal condition of the digestive system. In recent years, treatment concepts, methods, and strategies for the diagnosis of AP have advanced, and this has played an important role in promoting the standardization of AP diagnosis and treatment and improving the treatment quality of AP patients. On the basis of previous guidelines and expert consensus, this guideline adopts an evidence-based, problem-based expression; synthesizes important clinical research data at home and abroad in the most recent 5 years; and forms 29 recommendations through multidisciplinary expert discussion, including diagnosis, treatment, and follow-up. It is expected to provide evidence support for the treatment of AP in the clinical setting in China.